A long journey to effective obesity treatments: is there light at the end of the tunnel?. (May 2013) - Dodson, Michael V; Boudina, Sihem; Albrecht, Elke; Bucci, Luke; Culver, Melinda Fernyhough; Wei, Shengjuan; Bergen, Werner G; Amaral, Andreia J; Moustaid-Moussa, Naima; Poulos, Sylvia; Hausman, Gary J
As the obesity epidemic continues, more Americans are getting fatter, having more weight-related problems such as cardiovascular disease, and are experiencing new metabolic dysfunctions. For over 50 years, the adipose tissue (AT), commonly referred to as fat, has been of interest to academic and clinical scientists, public health officials and individuals interested in body composition and image including much of the average public, athletes, parents, etc. On one hand, efforts to alter body shape, weight and body fat percentage still include bizarre and scientifically unfounded methods. On the other hand, significant new scientific strides have been made in understanding the growth, function and regulation of anatomical and systemic AT. Markers of transition/conversion of precursor cells that mature to form lipid assimilating adipocytes have been identified. Molecular 'master' regulators such as peroxisome proliferator-activated receptor gamma and CCAAT-enhancer-binding proteins were uncovered and regulatory mechanisms behind variables of adiposity defined and refined. Interventions including pharmaceutical compounds, surgical, psychosocial interventions have also been tested. Has all of the preceding research helped alleviate the adverse physiologies of overweight and/or obese people? Does research to date point to new modalities that should be the focus of efforts to rid the world of obesity-related problems in the 21st century? This review provides a general overview of scientific efforts to date and a provocative view of the future for adiposity.